2001
DOI: 10.1016/s0079-6611(01)00069-6
|View full text |Cite
|
Sign up to set email alerts
|

Vertical structure, turbulent mixing and fluxes during Lagrangian observations of an upwelling filament system off Northwest Iberia

Abstract: In August 1998, a recurrent filament located near 42°N off Galicia was sampled as part of the OMEX-II project. Lagrangian and other observations were made on the shelf where the filament arose and offshore in the filament itself under upwelling favourable but fluctuating winds. The shelf drift experiment monitored a change from southward to weak northward net flow as the winds decreased to zero. Shipborne ADCP measurements showed that the shelf was supplying decreasing volumes of water to the filament as the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 18 publications
3
38
0
1
Order By: Relevance
“…During the second Lagrangian experiment the behaviour of this drifting buoy was compared with mixed layer Argos drifters drogued at 15m depth. This showed that the drifting buoy from PML was an efficient water mass marker (Joint et al, 2001a;Barton, Inall, Sherwin, & Torres, 2001). The first Lagrangian experiment started over the continental shelf on 3 August (42.62°N, 9.40°W) and the drifter moved southwards until 7 August (42.07°N, 9.44°W) when the experiment ended.…”
Section: Methodsmentioning
confidence: 93%
“…During the second Lagrangian experiment the behaviour of this drifting buoy was compared with mixed layer Argos drifters drogued at 15m depth. This showed that the drifting buoy from PML was an efficient water mass marker (Joint et al, 2001a;Barton, Inall, Sherwin, & Torres, 2001). The first Lagrangian experiment started over the continental shelf on 3 August (42.62°N, 9.40°W) and the drifter moved southwards until 7 August (42.07°N, 9.44°W) when the experiment ended.…”
Section: Methodsmentioning
confidence: 93%
“…Well-developed upwelling can form filaments taking surface water off-shelf, with complementary on-shelf flow (beside and below). Filament fluxes are typically O(0.6 Sv) each (Barton et al, 2001) exceeding the Ekman transport over the (semi-regular) spacing between filaments.…”
Section: West Iberiamentioning
confidence: 99%
“…Numerosos estudios han caracterizado diferentes eventos de afloramiento en la plataforma adyacente a estas rías (Blanton et al 1984;Tenore et al 1984;McClain et al 1986;Alvarez-Salgado et al 1993, 2000Perez et al 1995;Prego y Bao 1997;Prego et al 1999;Barton et al 2001;Alvarez et al 2008a) y también en su interior (Blanton et al 1987;Prego y Fraga 1992;Prego 1993aPrego , 1993bPrego , 1994Rosón et al 1995;Nogueira et al 1997aNogueira et al , 1997bDoval et al 1998;Pardo et al 2001;Prego et al 1995Prego et al , 2001deCastro et al 2004;Alvarez et al 2005). Consecuentemente, se puede resumir que el afloramiento en esta costa occidental gallega es un fenómeno frecuente durante los meses de primavera y verano que es resultado del régimen de vientos de componente norte que soplan a lo largo de la plataforma.…”
Section: Introductionunclassified